Өнөөгийн монгол хүний үнэлэмжийн зарим онцлог: Some characteristics of modern Mongolian judgments - Г., Буянтогтох (Mongolian Studies, 2023)
The values of any people are expressed through their national cultural heritage and mentality. Mentality is a true expression of cultural values and is distinct to each nations. Research on values is therefore extremely valuable in appreciating the qualities and characteristics of any nation’s mentality.